Efficacy of felodipine and enalapril in the treatment of essential hypertension with coronary artery disease and the effect on levels of Salusin-β, Apelin, and PON1 gene expression in patients - Zhang, Wanyi; Zhang, Jun; Jin, Feng; Zhou, Heng (Cellular and Molecular Biology, 2022)
This study aimed to analyze the effect of felodipine combined with enalapril in the treatment of patients with essential hypertension and coronary artery disease. Also, the effect of these medicines was evaluated on the peripheral blood Salusin-β, Apelin levels, and PON1 gene expression. For this purpose, 110 patients with essential hypertension combined with coronary heart disease, admitted to the hospital from January 2019 to January 2021, were selected and randomly divided into two groups. The control group was given felodipine treatment alone, and the study group was treated with combined application of felodipine and enalapril. The treatment effect, peripheral blood Salusin-β, Apelin, PON1 gene expression, and the safety of medication were compared between the two groups. The results showed that the post-treatment systolic blood pressure in the study group was 119.77 ± 5.23 mm Hg and diastolic blood pressure was 86.84 ± 5.42 mm Hg, both of which were significantly lower than those in the control group (127.81 ± 6.92 mm Hg and 95.13 ± 6.08 mm Hg), with statistically significant differences (p<0.05). The effective rates of the study group and the control group were 92.73% and 74.54% respectively, with statistically significant differences (P<0.05). The post-treatment peripheral blood Salusin-βlevel in the study group was 3.77±0.53mmol/L, and Apelin was 1.94±0.58μg/L, with statistically significant differences compared to the control group (P<0.05). The PON1 gene expression in the study group was higher than those in the control group after treatment (P<0.05). Also, the results showed that there was no statistical difference in adverse reactions between the two groups (P>0.05). According to these results, the combination of felodipine and enalapril in patients with essential hypertension combined with coronary artery disease can effectively lower the patients’ blood pressure and improve their peripheral blood Salusin-β, Apelin levels, and PON1 gene expression, thus enhancing the patients’ therapeutic effect with few adverse effects and high safety.